TOURISM IMPACT ON REEF FLATS IN PORTO DE GALINHAS BEACH, PERNAMBUCO, BRAZIL - Barradas, Juliana Imenis; Amaral, Fernanda Duarte; Hernández, Malva Isabel; Flores-Montes, Manuel Jesus; Steiner, Andrea Quirino (Arquivos de Ciências do Mar, 2012)
Approximately 60% of coral reefs are currently threatened by several natural and anthropogenic impacts. One of the fastest growing industries in the world and a great producer of organic waste, tourism can have negative impacts on biodiversity and on the functioning of reef ecosystems. This study aimed to find possible anthropogenic impacts related to tourism in reef environments of northeastern of Brazil (Porto de Galinhas Beach, Pernambuco). Water samples were collected for salinity, pH, dissolved inorganic nutrients (ammonium, nitrite, nitrate, phosphate, and silicate), and chlorophyll a analyses during the high and low-season tourism calendar. A greater concentration of ammonium, nitrate, and phosphate was verified during the high tourist season, whereas nitrite, silicate, and chlorophyll a were highest during low tourist season. Trampling and other recreational activities harmful to reefs were also observed in the area.